New magnetic fabric data from Almora crystalline rocks around Rameshwar, Near North Almora Thrust - Katiyar, Vibha; Patil, S.K.; Srivastava, Hari B. (My University, 2020)
In this paper, Anisotropy of Magnetic Susceptibility (AMS) data from the rocks of Almora crystalline in the vicinity of Rameshwar is presented. The study integrates field, micro structural and Anisotropy of Magnetic Susceptibility (AMS) studies. Field foliation strike shows NW-SE orientation with moderate to high dip in rocks of Almora Crystalline, whereas near North Almora Thrust rocks of Almora Crystalline are steeply dipping and litho-units are intensely mylonitized due to NE-SW regional compression. The magnetic foliations are recorded to be parallel to the field foliation of the study area. Variation in orientation of magnetic lineation is inferred to imply superposed deformation in the study area. AMS study also reveals that the shape of susceptibility ellipsoid is oblate which is inferred to be due to compression.
Keywords: Anisotropy of magnetic susceptibility; Almora Crystalline Rocks